2023
DOI: 10.1177/21501351221122972
|View full text |Cite
|
Sign up to set email alerts
|

Isolated Vascular Rings Are Common Cardiovascular Malformations

Abstract: Objective We investigated the prevalence of isolated vascular rings in the general population of Southern Nevada. Methods We identified those prenatally and postnatally diagnosed with an isolated vascular ring between January 2014 and December 2021. We included only those with vascular or ligamentous structures completely encircling the trachea and esophagus. To investigate the prevalence of isolated vascular rings, we included only those with situs solitus, levocardia, and no significant intracardiac malforma… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(5 citation statements)
references
References 14 publications
0
5
0
Order By: Relevance
“…Published data estimate the prevalence of a VR at about 7 per 10,000 live births (1). The incidence of the DAA in the literature is 1.5 per 10,000.…”
Section: Discussionmentioning
confidence: 98%
“…Published data estimate the prevalence of a VR at about 7 per 10,000 live births (1). The incidence of the DAA in the literature is 1.5 per 10,000.…”
Section: Discussionmentioning
confidence: 98%
“…With the rich experience of prenatal diagnosis, the use of three-vessel tracheotomy for the diagnosis of vascular ring diseases has been widely recognized in recent years [ 14 ]. It has been reported that the prenatal detection rate of isolated vascular rings has increased from 2.4 to 10,000 to 7 per 10,000 [ 8 ]. But there are still misdiagnoses and missed diagnoses of vascular rings.…”
Section: Discussionmentioning
confidence: 99%
“…Early diagnosis of congenital vascular rings is intended to improve the symptoms of compression in patients with airway compression [ 19 ]. With the increase of prenatal detection rate of vascular rings, the incidence of rare diseases has been realized to be twice that of tetralogy of Fallot [ 8 ], and the evaluation of the relationship between vascular rings and airways is more important. However, there are few articles on the prenatal diagnosis of vascular ring diseases and with qualitative or quantitative assessments of airway prognosis in PubMed [ 10 ].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Vascular rings present with a frequency as high as seven in 10,000 live births. 1 Contemporary fetal detection and use of computed tomography (CT) have led to increased early detection of these lesions and earlier repair in many centers. 2 Right aortic arch with aberrant left subclavian artery (RAA-ALSA) is a common form of vascular ring (15%-25%), and different surgical techniques have been proposed to repair the lesion.…”
Section: Introductionmentioning
confidence: 99%